The advanced treatment of hydrogen bonding in quantum crystallography. Issue 3 (2nd May 2021) - Malaspina, Lorraine A.; Genoni, Alessandro; Jayatilaka, Dylan; Turner, Michael J.; Sugimoto, Kunihisa; Nishibori, Eiji; Grabowsky, Simon
Abstract : Hydrogen‐bonding parameters are modelled with different methods of quantum crystallography. The underlying model assumptions are analysed and related to the refinement results. Abstract : Although hydrogen bonding is one of the most important motifs in chemistry and biology, H‐atom parameters are especially problematic to refine against X‐ray diffraction data. New developments in quantum crystallography offer a remedy. This article reports how hydrogen bonds are treated in three different quantum‐crystallographic methods: Hirshfeld atom refinement (HAR), HAR coupled to extremely localized molecular orbitals and X‐ray wavefunction refinement. Three different compound classes that form strong intra‐ or intermolecular hydrogen bonds are used as test cases: hydrogen maleates, the tripeptide l ‐alanyl‐glycyl‐l ‐alanine co‐crystallized with water, and xylitol. The differences in the quantum‐mechanical electron densities underlying all the used methods are analysed, as well as how these differences impact on the refinement results.